Wild boar paradise - Erikoinen, Matti; Erikoinen, Pekka (2014)
Due to the growing wild boar (Sus scrofa L.) population in Sweden there has been an increase in wild boar related traffic accidents, damage on cropland, and conflicts regarding the management of the wild boar. Knowing what makes the wild boar reproduce and survive more or less successfully in different geographic areas is an important part of managing the population. According to previous studies the wild boars rate of increase varies from county to county. The aim of this study was to test, on the county scale level, if landscape composition and diversity as well as people and hunter densities might be the reason for this variation. The first hypothesis was that a big proportion of forests and cropland would increase the rate of increase. The second was that the more diverse the landscape, the higher the rate of increase. The third hypothesis was that a higher people and hunter density would mean a lower rate of increase. Analyses were done on the 14 counties where there is an established wild boar population. The programs used to carry out the analyses were ArcMap, FRAGSTATS and JMP. The results show that in terms of protected areas, the landscape composition might have an effect on the wild boar’s rate of increase. When testing the factor “landscape diversity” the “landscape division index” was positively correlated with the rate of increase. People density did not have a significant correlation with the rate of increase, while hunter density did account for some of the variation in the rate of increase. We suggest that further studies should be made with the same kind of landscape metrics we tested for in this study, but on a finer scale of sub-landscapes within each county.